Polarizing film, polarizing plate, and method for producing polarizing film

By using a polyvinyl alcohol-based resin film with dichromatic substances in the polarizing film and adopting a multi-stage stretching and drying shrinkage treatment process, the problem of the polarizing film being prone to crack along the absorption axis direction is solved, and a polarizing film with high puncture intensity and excellent optical characteristics is achieved.

CN119861444AActive Publication Date: 2025-04-22NITTO DENKO CORP
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202510108354.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2019-02-08
Filing Date
2020-02-06
Publication Date
2025-04-22
Estimated Expiration
2040-02-06

AI Technical Summary

Technical Problem

The existing polarizing films are prone to cracking along the absorption axis direction, resulting in damage.

Method used

The polarizing film made of polyvinyl alcohol-based resin film containing dichromatic substances has a high puncture intensity by using an orientation function of 0.30 or less.

Benefits of technology

The breakage of the polarizing film along the absorption axis direction is significantly suppressed, and its bending and durability are improved, while taking into account acceptable optical characteristics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119861444A_ABST
    Figure CN119861444A_ABST
Patent Text Reader

Abstract

Provided is a polarizing film in which breakage in the absorption axis direction is suppressed. The polarizing film according to the present invention comprises a polyvinyl alcohol resin film containing a dichroic substance, and has an orientation function of 0.30 or less. In one embodiment, the thickness of the polarizing film is 8 [mu] m or less. A polarizing plate according to the present invention comprises the polarizing film and a protective layer disposed on at least one side of the polarizing film.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application of an application with an application date of February 6, 2020, application number 202080012812.1, and invention name “Polarizing film, polarizing plate, and method for manufacturing the polarizing film”. Technical Field

[0002] The present invention relates to a polarizing film, a polarizing plate, and a method for manufacturing the polarizing film. Background Art

[0003] In a liquid crystal display device, which is a representative image display device, polarizing films are arranged on both sides of the liquid crystal unit due to its image forming method. As a method for manufacturing a polarizing film, for example, the following method is proposed: a laminate having a resin substrate and a polyvinyl alcohol (PVA) resin layer is stretched, and then dyed to obtain a polarizing film on the resin substrate (for example, Patent Document 1). Using such a method, a thin polarizing film can be obtained, and therefore it has attracted attention as a method that contributes to the thinning of image display devices in recent years. However, the thin polarizing film as described above has the problem of being easily cracked (easily damaged) along the absorption axis direction.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Application Publication No. 2001-343521 Summary of the invention

[0007] Problem that the invention aims to solve

[0008] The present invention has been made to solve the above-mentioned conventional problems, and a main object of the present invention is to provide a polarizing film in which breakage along the absorption axis direction is suppressed.

[0009] Solutions for solving problems

[0010] The polarizing film according to the embodiment of the present invention is composed of a polyvinyl alcohol-based resin film containing a dichroic substance, and has an orientation function of 0.30 or less.

[0011] In one embodiment, the polarizing film has a thickness of 8 μm or less.

[0012] In one embodiment, the polarizing film has a single body transmittance of 40.0% or more and a degree of polarization of 99.0% or more.

[0013] In one embodiment, the polarizing film has a puncture strength of 30 gf / μm or more.

[0014] A polarizing film according to another embodiment of the present invention is composed of a polyvinyl alcohol-based resin film containing a dichroic substance, and has a puncture strength of 30 gf / μm or more.

[0015] According to another aspect of the present invention, a polarizing plate is provided, comprising: the polarizing film described above, and a protective layer disposed on at least one side of the polarizing film.

[0016] According to another aspect of the present invention, a method for manufacturing the above-mentioned polarizing film is provided. The manufacturing method comprises: forming a polyvinyl alcohol resin layer containing iodide or sodium chloride and polyvinyl alcohol resin on one side of a long strip of thermoplastic resin substrate to form a laminate; and sequentially subjecting the laminate to an air auxiliary stretching treatment, a dyeing treatment, an underwater stretching treatment, and a drying shrinkage treatment, wherein the drying shrinkage treatment is performed by heating the laminate while conveying the laminate in the length direction, thereby shrinking the laminate in the width direction by more than 2%. The total stretching ratio of the air auxiliary stretching treatment and the underwater stretching treatment is 3.0 to 4.5 times relative to the original length of the laminate; the stretching ratio of the air auxiliary stretching treatment is greater than the stretching ratio of the underwater stretching treatment.

[0017] Effects of the Invention

[0018] According to the present invention, by setting the orientation function to less than 0.30 or by setting the piercing strength to more than 30 gf / μm, a polarizing film in which the fracture along the absorption axis direction is suppressed can be realized. In the past, it was difficult to obtain acceptable optical properties (representatively, single-unit transmittance and polarization degree) for a polarizing film with such a small orientation function, but according to the present invention, it is possible to take into account both such a small orientation function and acceptable optical properties. Furthermore, according to the present invention, it is possible to take into account both such a large piercing strength and acceptable optical properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 This is a schematic cross-sectional view of a polarizing plate according to one embodiment of the present invention.

[0020] Figure 2 This is a schematic diagram showing an example of a drying shrinkage process using a heating roller. DETAILED DESCRIPTION

[0021] Hereinafter, embodiments of the present invention will be described, but the present invention is not limited to these embodiments.

[0022] A.Polarizing film

[0023] The polarizing film of the embodiment of the present invention is composed of a polyvinyl alcohol (PVA) resin film containing a dichroic substance (representatively iodine, dichroic dye), and the orientation function is 0.30 or less. When it is such a structure, the polarizing film can be significantly suppressed from cracking (damage) along the absorption axis direction. As a result, a polarizing film (resulting in a polarizing plate) with excellent bending properties can be obtained. Such a polarizing film (resulting in a polarizing plate) can be applied to a preferably curved image display device, a more preferably bendable image display device, and a further preferably foldable image display device. The orientation function is, for example, less than 0.25, preferably less than 0.22, more preferably less than 0.20, further preferably less than 0.18, and particularly preferably less than 0.15. The lower limit of the orientation function can be, for example, 0.05. If the orientation function is too small, sometimes an acceptable monomer transmittance and / or degree of polarization cannot be obtained.

[0024] The orientation function (f) can be obtained, for example, by using a Fourier transform infrared spectrometer (FT-IR) and attenuated total reflection (ATR) measurement with polarized light as the measurement light. Specifically, the measurement is carried out in a state where the stretching direction of the polarizing film is parallel and perpendicular to the polarization direction of the measurement light, and the 2941 cm-1 absorbance spectrum is used. -1 The intensity I is calculated by the following formula. Here, the intensity I is based on 3330cm -1 The reference peak is 2941cm -1 / 3330cm -1 It should be noted that when f = 1, it is completely oriented, and when f = 0, it is random. In addition, it is considered that 2941cm -1 The peak is due to the absorption of the vibration of the main chain (-CH2-) of PVA in the polarizing film.

[0025] f=(3 <cos 2 θ>-1) / 2

[0026] =(1-D) / [c(2D+1)]

[0027] =-2×(1-D) / (2D+1)

[0028] in,

[0029] c=(3cos 2 β-1) / 2,2941cm -1 In the case of vibration, β = 90°.

[0030] θ: Angle of the molecular chain relative to the stretching direction

[0031] β: Angle of the transition dipole moment relative to the molecular chain axis

[0032] D=(I ⊥ ) / (I / / ) (In this case, the more oriented the PVA molecules are, the larger D becomes)

[0033] I ⊥ :Measure the absorption intensity when the polarization direction of light is perpendicular to the stretching direction of the polarizing film

[0034] I / / :Measure the absorption intensity when the polarization direction of light is parallel to the stretching direction of the polarizing film

[0035] The thickness of the polarizing film is preferably 8 μm or less, more preferably 7 μm or less, further preferably 5 μm or less, particularly preferably 3 μm or less, and particularly preferably 2 μm or less. The lower limit of the thickness of the polarizing film may be, for example, 1 μm. The thickness of the polarizing film may be 2 μm to 6 μm in one embodiment, 2 μm to 4 μm in another embodiment, 2 μm to 3 μm in another embodiment, 5.5 μm to 7.5 μm in another embodiment, and 6 μm to 7.2 μm in another embodiment. By making the thickness of the polarizing film very thin in this way, thermal shrinkage can be made very small. It is speculated that such a structure also helps to suppress fractures in the absorption axis direction.

[0036] The polarizing film preferably shows absorption dichroism at any wavelength in the wavelength range of 380nm to 780nm. The monomer transmittance of the polarizing film is preferably 40.0% or more, more preferably 41.0% or more. The upper limit of the monomer transmittance can be, for example, 49.0%. The monomer transmittance of the polarizing film is 40.0% to 45.0% in one embodiment. The polarization degree of the polarizing film is preferably 99.0% or more, more preferably 99.4% or more. The upper limit of the polarization degree can be, for example, 99.999%. The polarization degree of the polarizing film is 99.0% to 99.99% in one embodiment. According to the present invention, although the orientation function is very small as described above, such a practically acceptable monomer transmittance and polarization degree can be achieved. It is speculated that this is because of the manufacturing method described later. It should be noted that the monomer transmittance is representatively the Y value obtained by measuring using an ultraviolet visible spectrophotometer and performing visual sensitivity correction. The degree of polarization is typically determined by the following equation based on the parallel transmittance Tp and the orthogonal transmittance Tc obtained by measuring with an ultraviolet-visible spectrophotometer and performing sensitivity correction.

[0037] Polarization degree (%) = {(Tp-Tc) / (Tp+Tc)} 1 / 2 ×100

[0038] The puncture strength of the polarizing film is 30 gf / μm or more, preferably 35 gf / μm or more, more preferably 40 gf / μm or more, further preferably 45 gf / μm or more, and particularly preferably 50 gf / μm or more. The upper limit of the puncture strength can be, for example, 80 gf / μm. By setting the puncture strength of the polarizing film to such a range, it is possible to significantly inhibit the polarizing film from cracking along the absorption axis direction. As a result, a polarizing film (resulting in a polarizing plate) with very excellent bending properties can be obtained. The puncture strength indicates the rupture resistance of the polarizing film when the polarizing film is pierced with a specified strength. The puncture strength can be expressed, for example, as the strength (fracture strength) of the rupture of the polarizing film when a specified needle is installed in a compression testing machine and the needle is pierced through the polarizing film at a specified speed. It should be noted that, according to the unit, it can be clearly understood that the puncture strength refers to the puncture strength per unit thickness (1 μm) of the polarizing film.

[0039] The polarizing film is composed of a PVA-based resin film containing iodine as described above. Preferably, the PVA-based resin constituting the PVA-based resin film (substantially a polarizing film) contains a PVA-based resin modified by acetoacetyl. When it is such a structure, a polarizing film with a desired puncture strength can be obtained. When the PVA-based resin as a whole is set to 100% by weight, the blending amount of the PVA-based resin modified by acetoacetyl is preferably 5% to 20% by weight, more preferably 8% to 12% by weight. When the blending amount is in such a range, the puncture strength can be set to a more appropriate range.

[0040] The polarizing film can be typically made using a laminate of more than two layers. As a specific example of a polarizing film obtained using a laminate, there can be cited a polarizing film obtained using a laminate of a resin substrate and a PVA-based resin layer formed by coating the resin substrate. The polarizing film obtained using a laminate of a resin substrate and a PVA-based resin layer formed by coating the resin substrate can be made, for example, as follows: a PVA-based resin solution is applied to a resin substrate and dried to form a PVA-based resin layer on the resin substrate, thereby obtaining a laminate of the resin substrate and the PVA-based resin layer; the laminate is stretched and dyed to make the PVA-based resin layer into a polarizing film. In the present embodiment, it is preferred that a polyvinyl alcohol-based resin layer containing a halide and a polyvinyl alcohol-based resin is formed on one side of the resin substrate. Stretching typically includes immersing the laminate in an aqueous boric acid solution and stretching it. Furthermore, stretching preferably also includes stretching the laminate in the air at a high temperature (e.g., above 95°C) before stretching in the aqueous boric acid solution. In an embodiment of the present invention, the total stretching ratio is, for example, 3.0 to 4.5 times, which is significantly smaller than the usual ratio. Even with such a total stretching ratio, a polarizing film with acceptable optical properties can be obtained by combining the addition of a halide and a drying shrinkage treatment. Furthermore, in an embodiment of the present invention, the stretching ratio of the air-assisted stretching is greater than the stretching ratio of the boric acid water stretching. By adopting such a structure, a polarizing film with acceptable optical properties can be obtained even if the total stretching ratio is small. Furthermore, the laminate is preferably provided with a drying shrinkage treatment in which the laminate is transported in the length direction while being heated so as to shrink by more than 2% in the width direction. In one embodiment, the method for manufacturing a polarizing film comprises: sequentially subjecting the laminate to an air-assisted stretching treatment, a dyeing treatment, an underwater stretching treatment, and a drying shrinkage treatment. By introducing auxiliary stretching, the crystallinity of PVA can be improved even if PVA is coated on a thermoplastic resin, and high optical properties can be achieved. In addition, by simultaneously improving the orientation of PVA in advance, the problems such as the reduction and dissolution of the orientation of PVA can be prevented when immersed in water in the subsequent dyeing process and stretching process, and high optical properties can be achieved. Furthermore, when the PVA-based resin layer is immersed in a liquid, the disorder of the orientation of the polyvinyl alcohol molecules and the reduction of the orientation can be suppressed compared with the case where the PVA-based resin layer does not contain a halide. Thus, the optical properties of the polarizing film obtained by the treatment process of immersing the laminate in a liquid such as dyeing treatment and underwater stretching treatment can be improved. Furthermore, by utilizing a drying shrinkage treatment to shrink the laminate in the width direction, the optical properties can be improved. The obtained laminate of the resin substrate / polarizing film can be used directly (that is, the resin substrate can be used as a protective layer of the polarizing film), or the resin substrate can be peeled off from the laminate of the resin substrate / polarizing film and any appropriate protective layer that meets the purpose can be stacked on the peeling surface and used. The details of the method for manufacturing the polarizing film will be described in item C later.

[0041] B.Polarizing plate

[0042] Figure 1 1 is a schematic cross-sectional view of a polarizing plate according to an embodiment of the present invention. The polarizing plate 100 comprises: a polarizing film 10, a first protective layer 20 disposed on one side of the polarizing film 10, and a second protective layer 30 disposed on the other side of the polarizing film 10. The polarizing film 10 is the polarizing film of the present invention described in the above-mentioned item A. One of the first protective layer 20 and the second protective layer 30 may be omitted. It should be noted that, as described above, one of the first protective layer and the second protective layer may be a resin substrate used in the manufacture of the above-mentioned polarizing film.

[0043] The first and second protective layers are formed by any appropriate film that can be used as a protective layer of a polarizing film. For the specific example of the material as the main component of the film, cellulose resins such as triacetyl cellulose (TAC), polyester resins, polyvinyl alcohol resins, polycarbonate resins, polyamide resins, polyimide resins, polyethersulfone resins, polysulfone resins, polystyrene resins, polynorbornene resins, polyolefin resins, (meth) acrylic acid resins, acetate resins, etc. can be listed. In addition, thermosetting resins or ultraviolet curing resins such as (meth) acrylic acid resins, carbamate resins, (meth) acrylic acid carbamate resins, epoxy resins, and silicone resins can also be listed. In addition, for example, glassy polymers such as siloxane polymers can also be listed. In addition, the polymer film described in Japanese Patent Publication No. 2001-343529 (WO01 / 37007) can also be used. As the material of the film, for example, a resin composition containing a thermoplastic resin having a substituted or unsubstituted imide group in the side chain and a thermoplastic resin having a substituted or unsubstituted phenyl group and a nitrile group in the side chain can be used, for example, a resin composition containing an alternating copolymer formed by isobutylene and N-methylmaleimide and an acrylonitrile-styrene copolymer can be cited. The polymer film can be, for example, an extrusion molding of the above resin composition.

[0044] When the polarizing plate 100 is applied to an image display device, the thickness of the protective layer (outer protective layer) disposed on the side opposite to the display panel is typically 300 μm or less, preferably 100 μm or less, more preferably 5 μm to 80 μm, and further preferably 10 μm to 60 μm. It should be noted that, when the surface treatment is performed, the thickness of the outer protective layer is the thickness including the thickness of the surface treatment layer.

[0045] When the polarizing plate 100 is applied to an image display device, the thickness of the protective layer (inner protective layer) disposed on the display panel side is preferably 5 μm to 200 μm, more preferably 10 μm to 100 μm, and further preferably 10 μm to 60 μm. In one embodiment, the inner protective layer is a phase difference layer having any appropriate phase difference value. In this case, the in-plane phase difference Re (550) of the phase difference layer is, for example, 110 nm to 150 nm. "Re (550)" is the in-plane phase difference measured at 23 ° C with light of a wavelength of 550 nm, and is calculated by the formula: Re = (nx-ny) × d. Here, "nx" is the refractive index in the direction where the refractive index in the plane is the largest (ie, the slow axis direction), "ny" is the refractive index in the direction orthogonal to the slow axis in the plane (ie, the fast axis direction), "nz" is the refractive index in the thickness direction, and "d" is the thickness (nm) of the layer (film).

[0046] C. Method for manufacturing polarizing film

[0047] The manufacturing method of the polarizing film of one embodiment of the present invention comprises: forming a polyvinyl alcohol resin layer (PVA resin layer) containing a halide and a polyvinyl alcohol resin (PVA resin) on one side of a long thermoplastic resin substrate to form a laminate; and sequentially subjecting the laminate to an air auxiliary stretching treatment, a dyeing treatment, an underwater stretching treatment and a drying shrinkage treatment, wherein the drying shrinkage treatment is performed by heating the laminate while conveying the laminate in the length direction, thereby shrinking the laminate in the width direction by more than 2%. The content of the halide in the PVA resin layer is preferably 5 to 20 parts by weight relative to 100 parts by weight of the PVA resin. The drying shrinkage treatment is preferably performed using a heating roller, and the temperature of the heating roller is preferably 60°C to 120°C. The shrinkage rate of the laminate in the width direction caused by the drying shrinkage treatment is preferably more than 2%. According to such a manufacturing method, the polarizing film described in the above-mentioned item A can be obtained. In particular, by preparing a laminate having a PVA-based resin layer containing a halide, stretching the laminate through a multi-stage stretching process including auxiliary stretching in the air and stretching in water, and heating the stretched laminate with a heating roller, a polarizing film having excellent optical properties (representatively, monomer transmittance and unit absorbance) can be obtained.

[0048] C-1. Preparation of laminate

[0049] As a method for producing a laminate of a thermoplastic resin substrate and a PVA-based resin layer, any appropriate method may be adopted. Preferably, a coating solution containing a halide and a PVA-based resin is applied to the surface of the thermoplastic resin substrate and dried to form a PVA-based resin layer on the thermoplastic resin substrate. As described above, the content of the halide in the PVA-based resin layer is preferably 5 to 20 parts by weight relative to 100 parts by weight of the PVA-based resin.

[0050] As a coating method of the coating liquid, any appropriate method can be adopted. For example, roll coating, spin coating, wire bar coating, dip coating, die coating, curtain coating, spray coating, knife coating (comma coating, etc.) and the like can be listed. The coating and drying temperature of the above-mentioned coating liquid is preferably 50° C. or above.

[0051] The thickness of the PVA resin layer is preferably 2 μm to 30 μm, more preferably 2 μm to 20 μm. By making the thickness of the PVA resin layer before stretching very thin and reducing the total stretching ratio as described below, a polarizing film having acceptable monomer transmittance and polarization degree can be obtained even if the orientation function is very small.

[0052] Before forming the PVA-based resin layer, the thermoplastic resin substrate may be subjected to a surface treatment (e.g., corona treatment), or an easy-adhesive layer may be formed on the thermoplastic resin substrate. By carrying out such a treatment, the adhesion between the thermoplastic resin substrate and the PVA-based resin layer can be improved.

[0053] C-1-1. Thermoplastic resin substrate

[0054] As the thermoplastic resin substrate, any appropriate thermoplastic resin film may be used. Details of the thermoplastic resin substrate are described in, for example, Japanese Patent Application Laid-Open No. 2012-73580. The entire contents of the publication are incorporated herein by reference.

[0055] C-1-2. Coating liquid

[0056] The coating liquid contains a halide and a PVA-based resin as described above. The coating liquid is typically a solution in which the halide and the PVA-based resin are dissolved in a solvent. As the solvent, for example, water, dimethyl sulfoxide, dimethylformamide, dimethylacetamide, N-methylpyrrolidone, various glycols, polyols such as trimethylolpropane, amines such as ethylenediamine and diethylenetriamine can be cited. These can be used alone or in combination of two or more. Among these, water is preferred. The PVA-based resin concentration of the solution is preferably 3 to 20 parts by weight relative to 100 parts by weight of the solvent. At such a resin concentration, a uniform coating film that is closely attached to the thermoplastic resin substrate can be formed. The content of the halide in the coating liquid is preferably 5 to 20 parts by weight relative to 100 parts by weight of the PVA-based resin.

[0057] The coating liquid may be mixed with additives. As additives, for example, plasticizers, surfactants, etc. may be cited. As plasticizers, for example, polyols such as ethylene glycol and glycerol may be cited. As surfactants, for example, nonionic surfactants may be cited. These may be used for the purpose of further improving the uniformity, dyeability, and stretchability of the obtained PVA-based resin layer.

[0058] As the above-mentioned PVA-based resin, any appropriate resin can be used. For example, polyvinyl alcohol and ethylene-vinyl alcohol copolymer can be listed. Polyvinyl alcohol is obtained by saponifying polyvinyl acetate. Ethylene-vinyl alcohol copolymer is obtained by saponifying ethylene-vinyl acetate copolymer. The saponification degree of PVA-based resin is usually 85 mol% to 100 mol%, preferably 95.0 mol% to 99.95 mol%, and more preferably 99.0 mol% to 99.93 mol%. The saponification degree can be calculated according to JIS K 6726-1994. By using a PVA-based resin with such a saponification degree, a polarizing film with excellent durability can be obtained. When the saponification degree is too high, there is a concern that gelation will occur. As described above, the PVA-based resin preferably includes a PVA-based resin modified with an acetoacetyl group.

[0059] The average polymerization degree of the PVA-based resin can be appropriately selected depending on the purpose. The average polymerization degree is usually 1000 to 10000, preferably 1200 to 4500, and more preferably 1500 to 4300. The average polymerization degree can be determined in accordance with JIS K 6726-1994.

[0060] As the above-mentioned halide, any appropriate halide can be used. For example, iodide and sodium chloride can be listed. As the iodide, for example, potassium iodide, sodium iodide, and lithium iodide can be listed. Among these, potassium iodide is preferred.

[0061] The amount of the halide in the coating solution is preferably 5 to 20 parts by weight, more preferably 10 to 15 parts by weight, based on 100 parts by weight of the PVA resin. If the amount of the halide exceeds 20 parts by weight, the halide may bleed out, and the resulting polarizing film may become cloudy.

[0062] Generally, by stretching the PVA resin layer, the orientation of the polyvinyl alcohol molecules in the PVA resin will become higher, but if the stretched PVA resin layer is immersed in a liquid containing water, the orientation of the polyvinyl alcohol molecules is sometimes disordered and the orientation is reduced. In particular, when a laminate of a thermoplastic resin and a PVA resin layer is stretched in boric acid water, in order to stabilize the stretching of the thermoplastic resin, when the laminate is stretched in boric acid water at a relatively high temperature, the tendency for the above-mentioned orientation to decrease is significant. For example, the stretching of the PVA film itself in boric acid water is usually carried out at 60°C, while the stretching of the laminate of A-PET (thermoplastic resin substrate) and the PVA resin layer is carried out at a high temperature of about 70°C. In this case, the orientation of the PVA at the initial stage of stretching will decrease in the stage before it rises by stretching in water. In this regard, by preparing a laminate of a PVA-based resin layer containing a halide and a thermoplastic resin substrate, and performing high-temperature stretching (auxiliary stretching) in air before stretching the laminate in boric acid water, the crystallization of the PVA-based resin in the PVA-based resin layer of the laminate after auxiliary stretching can be promoted. As a result, when the PVA-based resin layer is immersed in a liquid, the disorder of the orientation of the polyvinyl alcohol molecules and the reduction of the orientation can be suppressed compared to the case where the PVA-based resin layer does not contain a halide. As a result, the optical properties of the polarizing film obtained by the treatment process of immersing the laminate in a liquid such as dyeing treatment and underwater stretching treatment can be improved.

[0063] C-2. Aerial assisted stretching treatment

[0064] In particular, in order to obtain high optical properties, a two-stage stretching method combining dry stretching (auxiliary stretching) and boric acid water stretching is preferred. By introducing auxiliary stretching as in the two-stage stretching, it is possible to stretch while suppressing the crystallization of the thermoplastic resin substrate. Furthermore, when PVA-based resin is applied to a thermoplastic resin substrate, in order to suppress the influence of the glass transition temperature of the thermoplastic resin substrate, it is necessary to lower the coating temperature compared to the case where PVA-based resin is usually applied on a metal roller. As a result, the crystallization of the PVA-based resin becomes relatively low and the problem of insufficient optical properties can be obtained. In response to this, by introducing auxiliary stretching, even when PVA-based resin is applied to a thermoplastic resin, the crystallinity of the PVA-based resin can be improved, and high optical properties can be achieved. In addition, by simultaneously improving the orientation of the PVA-based resin in advance, when immersed in water in subsequent dyeing processes and stretching processes, the problems of reduction and dissolution of the orientation of the PVA-based resin can be prevented, and high optical properties can be achieved.

[0065] The stretching method of aerial auxiliary stretching can be fixed-end stretching (for example, a method of stretching using a tenter stretching machine) or free-end stretching (for example, a method of uniaxially stretching the laminate by passing it between rollers with different circumferential speeds). In order to obtain high optical properties, free-end stretching can be actively adopted. In one embodiment, the aerial stretching process includes a heating roller stretching process, and the heating roller stretching process is stretched by transporting the above-mentioned laminate along its length direction while utilizing the circumferential speed difference between the heating rollers. The aerial stretching process typically includes a regional stretching process and a heating roller stretching process. It should be noted that the order of the regional stretching process and the heating roller stretching process is not limited, and the regional stretching process can be performed first, or the heating roller stretching process can be performed first. The regional stretching process can also be omitted. In one embodiment, the regional stretching process and the heating roller stretching process are performed sequentially. In addition, in another embodiment, in the tenter stretching machine, stretching is performed by holding the end of the film and expanding the distance between the tenters along the flow direction (the expansion of the distance between the tenters is the stretching ratio). At this time, the distance between the tenters in the width direction (perpendicular to the flow direction) is set in an arbitrarily close manner. It is preferred to set the stretch ratio in the flow direction in a manner closer to free-end stretching. In the case of free-end stretching, the shrinkage ratio in the width direction = (1 / stretch ratio) 1 / 2 to calculate.

[0066] The auxiliary stretching in the air can be carried out in one stage or in multiple stages. When it is carried out in multiple stages, the stretching ratio is the product of the stretching ratios of each stage. The stretching direction in the auxiliary stretching in the air is preferably substantially the same as the stretching direction in the underwater stretching.

[0067] The stretching ratio in the air-assisted stretching is preferably 1.0 to 4.0 times, more preferably 1.5 to 3.5 times, and further preferably 2.0 to 3.0 times. When the stretching ratio of the air-assisted stretching is in such a range, when combined with the stretching in water, the total stretching ratio can be set to the desired range, and the desired orientation function can be achieved. As a result, a polarizing film in which the breakage along the absorption axis direction is suppressed can be obtained. Furthermore, as described above, the stretching ratio of the air-assisted stretching is greater than the stretching ratio of the boric acid water stretching. By adopting such a structure, even if the total stretching ratio is small, a polarizing film with acceptable optical properties can be obtained.

[0068] The stretching temperature of the aerial auxiliary stretching can be set to any appropriate value according to the forming material of the thermoplastic resin substrate, the stretching method, etc. The stretching temperature is preferably above the glass transition temperature (Tg) of the thermoplastic resin substrate, more preferably above the glass transition temperature (Tg) of the thermoplastic resin substrate + 10 ° C, and particularly preferably above Tg + 15 ° C. On the other hand, the upper limit of the stretching temperature is preferably 170 ° C. By stretching at such a temperature, the crystallization of the PVA-based resin can be suppressed from proceeding rapidly, thereby suppressing the adverse conditions caused by the crystallization (for example, hindering the orientation of the PVA-based resin layer caused by stretching).

[0069] C-3. Insolubilization, dyeing and cross-linking

[0070] As needed, an insolubilization treatment is performed after the auxiliary stretching treatment in the air and between the stretching treatment in the water and the dyeing treatment. The above-mentioned insolubilization treatment is typically performed by immersing the PVA-based resin layer in an aqueous solution of boric acid. The above-mentioned dyeing treatment is typically performed by dyeing the PVA-based resin layer with a dichroic substance (typically iodine). As needed, a cross-linking treatment is performed after the dyeing treatment and before the stretching treatment in the water. The above-mentioned cross-linking treatment is typically performed by immersing the PVA-based resin layer in an aqueous solution of boric acid. Details about the insolubilization treatment, the dyeing treatment and the cross-linking treatment are recorded, for example, in Japanese Patent Gazette No. 2012-73580 (mentioned above).

[0071] C-4. Underwater stretching

[0072] The underwater stretching treatment is performed by immersing the laminate in a stretching bath. Through the underwater stretching treatment, the laminate can be stretched at a temperature lower than the glass transition temperature (typically about 80° C.) of the thermoplastic resin substrate and the PVA resin layer, and the PVA resin layer can be stretched while suppressing crystallization. As a result, a polarizing film with excellent optical properties can be manufactured.

[0073] The stretching method of the laminate can adopt any appropriate method. Specifically, it can be fixed end stretching or free end stretching (for example, a method of uniaxially stretching the laminate by passing the laminate between rollers with different peripheral speeds). Preferably, free end stretching is selected. The stretching of the laminate can be carried out in one stage or in multiple stages. When it is carried out in multiple stages, the total ratio of stretching is the product of the stretching ratios of each stage.

[0074] The underwater stretching is preferably performed by immersing the laminate in a boric acid aqueous solution (boric acid underwater stretching). By using a boric acid aqueous solution as a stretching bath, the PVA-based resin layer can be given rigidity that can withstand the tension applied during stretching and water resistance that is insoluble in water. Specifically, boric acid generates tetrahydroxyborate anions in an aqueous solution and cross-links with the PVA-based resin through hydrogen bonds. As a result, the PVA-based resin layer can be given rigidity and water resistance so that it can be stretched well, and a polarizing film with excellent optical properties can be manufactured.

[0075] The above-mentioned boric acid aqueous solution is preferably obtained by dissolving boric acid and / or a borate in water as a solvent. The boric acid concentration is preferably 1 to 10 parts by weight, more preferably 2.5 to 6 parts by weight, and particularly preferably 3 to 5 parts by weight relative to 100 parts by weight of water. By setting the boric acid concentration to 1 part by weight or more, the dissolution of the PVA-based resin layer can be effectively suppressed, and a polarizing film with higher characteristics can be obtained. It should be noted that an aqueous solution obtained by dissolving a boron compound such as borax, glyoxal, glutaraldehyde, etc. in a solvent other than boric acid or a borate can also be used.

[0076] It is preferred to mix an iodide in the stretching bath (boric acid aqueous solution). By mixing an iodide, the dissolution of iodine adsorbed on the PVA-based resin layer can be suppressed. Specific examples of iodide are as described above. The concentration of iodide is preferably 0.05 to 15 parts by weight, more preferably 0.5 to 8 parts by weight relative to 100 parts by weight of water.

[0077] The stretching temperature (liquid temperature of the stretching bath) is preferably 40°C to 85°C, more preferably 60°C to 75°C. At such a temperature, it is possible to stretch at a high ratio while suppressing the dissolution of the PVA-based resin layer. Specifically, as described above, the glass transition temperature (Tg) of the thermoplastic resin substrate is preferably above 60°C in terms of its relationship with the formation of the PVA-based resin layer. In this case, if the stretching temperature is lower than 40°C, there is a concern that stretching cannot be performed well even if the plasticization of the thermoplastic resin substrate brought about by water is taken into account. On the other hand, the higher the temperature of the stretching bath, the higher the solubility of the PVA-based resin layer becomes, and there is a concern that excellent optical properties cannot be obtained. The immersion time of the laminate in the stretching bath is preferably 15 seconds to 5 minutes.

[0078] The stretching ratio based on underwater stretching is preferably 1.0 to 3.0 times, more preferably 1.0 to 2.0 times, and further preferably 1.0 to 1.5 times. When the stretching ratio in the underwater stretching is in such a range, the total stretching ratio can be set to the desired range, and the desired orientation function can be achieved. As a result, a polarizing film in which the breakage along the absorption axis direction is suppressed can be obtained. The total stretching ratio (the total of the stretching ratios when the air auxiliary stretching and the water stretching are combined) is as described above, for example, 3.0 to 4.5 times, preferably 3.0 to 4.0 times, and more preferably 3.0 to 3.5 times, relative to the original length of the laminate. By adding a halide to the coating solution, adjusting the stretching ratios of the air auxiliary stretching and the water stretching, and appropriately combining the drying shrinkage treatment, even with such a total stretching ratio, a polarizing film with acceptable optical properties can be obtained.

[0079] C-5. Drying shrinkage treatment

[0080] The above-mentioned drying shrinkage treatment can be carried out by heating the region as a whole, or by heating the conveying roller (using the so-called heating roller) (heating roller drying method). It is preferred to use both of them. By using a heating roller for drying, the heating curling of the laminate can be effectively suppressed to manufacture a polarizing film with excellent appearance. Specifically, by drying the laminate along the heating roller, the crystallization of the above-mentioned thermoplastic resin substrate can be effectively promoted to increase the crystallinity, and even at a lower drying temperature, the crystallinity of the thermoplastic resin substrate can be well increased. As a result, the rigidity of the thermoplastic resin substrate increases, thereby becoming a state that can withstand the shrinkage of the PVA-based resin layer caused by drying, and curling can be suppressed. In addition, by using a heating roller, the laminate can be dried while maintaining a flat state, so that not only curling but also wrinkles can be suppressed. At this time, the laminate is shrunk in the width direction by the drying shrinkage treatment, thereby improving the optical properties. This is because the orientation of PVA and PVA / iodine complex can be effectively improved. The shrinkage rate of the laminate in the width direction due to the drying shrinkage treatment is preferably 1% to 10%, more preferably 2% to 8%, and particularly preferably 4% to 6%.

[0081] Figure 2 Schematic diagram showing an example of drying shrinkage treatment. In the drying shrinkage treatment, the laminate 200 is dried while being transported by the transport rollers R1 to R6 and the guide rollers G1 to G4 heated to a predetermined temperature. In the example shown in the figure, the transport rollers R1 to R6 are arranged in a manner to alternately and continuously heat the surface of the PVA resin layer and the surface of the thermoplastic resin substrate, but, for example, the transport rollers R1 to R6 may be arranged in a manner to continuously heat only one surface of the laminate 200 (for example, the surface of the thermoplastic resin substrate).

[0082] The drying conditions can be controlled by adjusting the heating temperature of the conveying roller (the temperature of the heating roller), the number of heating rollers, the contact time with the heating roller, etc. The temperature of the heating roller is preferably 60°C to 120°C, more preferably 65°C to 100°C, and particularly preferably 70°C to 80°C. It is possible to produce an optical laminate that can well increase the crystallinity of the thermoplastic resin, thereby well suppressing curling, and has very excellent durability. It should be noted that the temperature of the heating roller can be measured by a contact thermometer. Six conveying rollers are provided in the example shown in the figure, but there is no particular limitation as long as there are multiple conveying rollers. The conveying rollers are usually set to 2 to 40, preferably 4 to 30. The contact time (total contact time) between the laminate and the heating roller is preferably 1 second to 300 seconds, more preferably 1 to 20 seconds, and more preferably 1 to 10 seconds.

[0083] The heating roller can be set in a heating furnace (such as an oven) or in a normal production line (under room temperature environment). It is preferably set in a heating furnace equipped with air supply means. By combining the drying based on the heating roller and the hot air drying, the rapid temperature change between the heating rollers can be suppressed, and the shrinkage in the width direction can be easily controlled. The temperature of the hot air drying is preferably 30°C to 100°C. In addition, the hot air drying time is preferably 1 second to 300 seconds. The wind speed of the hot air is preferably about 10m / s to 30m / s. It should be noted that the wind speed is the wind speed in the heating furnace and can be measured by a mini blade type digital anemometer.

[0084] C-6. Other treatments

[0085] It is preferred that a cleaning treatment be performed after the underwater stretching treatment and before the drying shrinkage treatment. The cleaning treatment is typically performed by immersing the PVA-based resin layer in an aqueous potassium iodide solution.

[0086] Example

[0087] The present invention is described in detail below by way of examples, but the present invention is not limited to these examples. The measuring methods of various properties are as follows. It should be noted that, unless otherwise specified, the "parts" and "%" in the examples and comparative examples are by weight.

[0088] (1) Thickness

[0089] The thickness was measured using an interferometer film thickness meter (manufactured by Otsuka Electronics Co., Ltd., product name "MCPD-3000"). The calculation wavelength range used for thickness calculation was 400 nm to 500 nm, and the refractive index was 1.53.

[0090] (2) Orientation function

[0091] The polarizing films obtained in the examples and comparative examples were subjected to attenuated total reflection spectroscopy (ATR: attenuated total reflection) measurement on the surface of the polarizing film using a Fourier transform infrared spectrometer (FT-IR) (manufactured by PerkinElmer, trade name: "Frontier"), with polarized infrared light used as measuring light. Germanium was used as the microcrystal for bonding the polarizing film, and the incident angle of the measuring light was set to 45°. The calculation of the orientation function was performed according to the following steps. The incident polarized infrared light (measuring light) was used as polarized light (s-polarized light) vibrating parallel to the surface of the sample bonding the germanium crystals, and the stretching direction of the polarizing film was configured to be perpendicular (⊥) and parallel ( / / ) to the polarization direction of the measuring light, and each absorbance spectrum was measured. Based on the absorbance spectrum obtained, the absorption function at (3330cm -1 Intensity) is the reference (2941cm -1 Strength)I. ⊥ The absorbance spectrum (2941 cm) obtained when the polarizing film is arranged in a direction perpendicular (⊥) to the polarization direction of the measurement light is obtained. -1 Strength) / (3330cm -1 Intensity). In addition, I / / The absorbance spectrum (2941 cm) obtained when the stretching direction of the polarizing film is arranged parallel ( / / ) to the polarization direction of the measurement light. -1 Strength) / (3330cm -1 Intensity). Here, (2941cm -1 intensity) is 2770 cm, which is the bottom of the absorbance spectrum. -1 and 2990cm -1 2941cm when set as baseline -1 The absorbance (3330cm -1 Strength) is 2990cm -1 and 3650cm -1 3330cm when set as baseline -1 The absorbance of ⊥ and I / / , the orientation function f is calculated according to formula 1. It should be noted that when f = 1, it is completely oriented, and when f = 0, it is random. -1 The peak at 3330 cm is due to the absorption of the vibration of the main chain (-CH2-) of PVA in the polarizing film. -1 The peak is due to the absorption of vibration of the hydroxyl group of PVA.

[0092] (Formula 1)f=(3<cos2θ> -1) / 2

[0093] =(1-D) / [c(2D+1)]

[0094] in,

[0095] c=(3cos 2 β-1) / 2

[0096] Use 2941cm as above -1 In the case of

[0097] θ: Angle of the molecular chain relative to the stretching direction

[0098] β: Angle of the transition dipole moment relative to the molecular chain axis

[0099] D=(I ⊥ ) / (I / / )

[0100] I ⊥ :Measure the absorption intensity when the polarization direction of light is perpendicular to the stretching direction of the polarizing film

[0101] I / / :Measure the absorption intensity when the polarization direction of light is parallel to the stretching direction of the polarizing film

[0102] (3) Single-body transmittance and polarization

[0103] The polarizing film was peeled off from the laminate of the polarizing film / thermoplastic resin substrate used in the examples and comparative examples, and the single transmittance Ts, parallel transmittance Tp, and orthogonal transmittance Tc measured by the ultraviolet visible spectrophotometer ("V-7100" manufactured by JASCO Corporation) of the polarizing film were used as Ts, Tp, and Tc of the polarizing film, respectively. These Ts, Tp, and Tc are Y values ​​obtained by measuring the 2-degree field of view (C light source) of JISZ 8701 and performing visual sensitivity correction.

[0104] The polarization degree P is calculated from the obtained Tp and Tc by the following formula.

[0105] Polarization degree P (%) = {(Tp-Tc) / (Tp+Tc)} 1 / 2 ×100

[0106] Note that, similar measurements can be performed using a spectrophotometer such as "LPF-200" manufactured by Otsuka Electronics Co., Ltd., and it was confirmed that similar measurement results can be obtained using any spectrophotometer.

[0107] (4) Fracture strength

[0108] The polarizing film is peeled off from the laminate of the polarizing film / thermoplastic resin substrate used in the examples and comparative examples, and placed on a compression tester equipped with a needle (manufactured by Kato-tech, product name "NDG5" needle penetration force measurement model), and pierced at room temperature (23°C ± 3°C) at a piercing speed of 0.33 cm / sec. The strength when the polarizing film is broken is taken as the breaking strength (piercing strength). For the evaluation value, the breaking strength of 10 sample pieces is measured and the average value is used. It should be noted that the needle uses a front end diameter of 0.5R needle. The polarizing film to be measured is clamped and fixed from both sides of the polarizing film with a jig having a circular opening of about 11 mm in diameter, and the test is performed by piercing the center of the opening with a needle. The breaking strength per unit thickness is used as an indicator of the difficulty of breaking, and is evaluated according to the following criteria.

[0109] ○: Breaking strength exceeds 30 gf / μm

[0110] ×: Breaking strength is 30 gf / μm or less

[0111] [Example 1]

[0112] As the thermoplastic resin substrate, a long amorphous isophthalic acid copolymer polyethylene terephthalate film (thickness: 100 μm) with a water absorption of 0.75% and a Tg of about 75°C was used. One side of the resin substrate was subjected to corona treatment (treatment conditions: 55 W·min / m 2 ).

[0113] 13 parts by weight of potassium iodide was added to 100 parts by weight of a PVA-based resin prepared by mixing polyvinyl alcohol (polymerization degree 4200, saponification degree 99.2 mol%) and acetoacetyl-modified PVA (manufactured by Nippon Synthetic Chemical Industry Co., Ltd., trade name "GOHSEFIMER Z410") in a ratio of 9:1 to prepare a PVA aqueous solution (coating solution).

[0114] The PVA aqueous solution was applied to the corona-treated surface of the resin substrate and dried at 60° C. to form a 13 μm-thick PVA-based resin layer, thereby producing a laminate.

[0115] The obtained laminate was subjected to free-end uniaxial stretching to 2.4 times in the longitudinal direction (longitudinal direction) between rolls having different peripheral speeds in an oven at 130° C. (in-air auxiliary stretching treatment).

[0116] Next, the laminate was immersed in an insolubilization bath (boric acid aqueous solution prepared by mixing 4 parts by weight of boric acid with 100 parts by weight of water) at a liquid temperature of 40° C. for 30 seconds (insolubilization treatment).

[0117] Next, the film was immersed in a dyeing bath (an iodine aqueous solution prepared by mixing iodine and potassium iodide at a weight ratio of 1:7 to 100 parts by weight of water) at a liquid temperature of 30° C. for 60 seconds (dyeing treatment) at a concentration adjusted so that the single body transmittance (Ts) of the final polarizing film would be 41.6%.

[0118] Next, the sample was immersed in a crosslinking bath (boric acid aqueous solution prepared by mixing 3 parts by weight of potassium iodide and 5 parts by weight of boric acid with respect to 100 parts by weight of water) at a liquid temperature of 40° C. for 30 seconds (crosslinking treatment).

[0119] Thereafter, the laminate was immersed in an aqueous boric acid solution (boric acid concentration: 4.0 wt %, potassium iodide: 5.0 wt %) at a liquid temperature of 62°C and uniaxially stretched in the longitudinal direction (length direction) between rollers having different circumferential speeds to a total stretching ratio of 3.0 times (underwater stretching treatment: the stretching ratio in the underwater stretching treatment was 1.25 times).

[0120] Thereafter, the laminate was immersed in a cleaning bath (an aqueous solution prepared by mixing 4 parts by weight of potassium iodide with respect to 100 parts by weight of water) at a liquid temperature of 20° C. (cleaning treatment).

[0121] Thereafter, the laminate was brought into contact with a SUS heating roll having a surface temperature of 75° C. for about 2 seconds while being dried in an oven maintained at 90° C. (drying shrinkage treatment). The shrinkage rate in the width direction of the laminate due to the drying shrinkage treatment was 2%.

[0122] In this manner, a polarizing film having a thickness of 7.1 μm was formed on the resin substrate.

[0123] Table 1 shows the orientation function, single body transmittance, degree of polarization, and breaking strength of the obtained polarizing film.

[0124] [Example 2]

[0125] A polarizing film having a thickness of 6.6 μm was produced in the same manner as in Example 1 except that the stretching ratio in the underwater stretching treatment was 1.45 times and the total stretching ratio was 3.5 times. The obtained polarizing film was subjected to the same evaluation as in Example 1. The results are shown in Table 1.

[0126] [Example 3]

[0127] A polarizing film having a thickness of 6.1 μm was prepared in the same manner as in Example 1 except that the stretching ratio in the underwater stretching treatment was 1.67 times and the total stretching ratio was 4.0 times. The obtained polarizing film was evaluated in the same manner as in Example 1. The results are shown in Table 1.

[0128] [Example 4]

[0129] A polarizing film having a thickness of 5.6 μm was produced in the same manner as in Example 1 except that the stretching ratio in the underwater stretching treatment was 1.87 times and the total stretching ratio was 4.5 times. The obtained polarizing film was subjected to the same evaluation as in Example 1. The results are shown in Table 1.

[0130] [Comparative Example 1]

[0131] The same operation as in Example 1 was performed except that the stretching ratio of the underwater stretching treatment was set to 2.4 times, the total stretching ratio was set to 5.5 times, and the liquid temperature of the stretching bath was set to 70°C, to prepare a polarizing film with a thickness of 5.0 μm. It should be noted that the width residual rate of the obtained polarizing film was 48% (the shrinkage rate in the width direction was 52%). The obtained polarizing film was subjected to the same evaluation as in Example 1. The results are shown in Table 1.

[0132] [Comparative Example 2]

[0133] A polarizing film having a thickness of 5.5 μm was produced in the same manner as in Comparative Example 1 except that the width residual rate was 43% (the shrinkage rate in the width direction was 57%). The obtained polarizing film was subjected to the same evaluation as in Example 1. The results are shown in Table 1.

[0134] [Comparative Example 3]

[0135] A long roll of a 30 μm thick PVA resin film (manufactured by KURARAY CO., LTD, product name "PE3000") was uniaxially stretched along the long side direction with a roll stretching machine in a manner such that the total stretching ratio was 6.0 times, and swelling, dyeing, crosslinking and washing treatments were performed at the same time, and finally drying treatment was performed to produce a polarizer with a thickness of 12 μm. The obtained polarizer was subjected to the same evaluation as in Example 1. The results are shown in Table 1.

[0136] [Table 1]

[0137]

[0138] It is clear from Table 1 that the polarizing film of the embodiment of the present invention has a single transmittance and polarization degree that are practically acceptable, and has a very high breaking strength along the absorption axis direction. Such a breaking strength means that the polarizing film is not easy to be cracked along the absorption axis direction.

[0139] Industrial Applicability

[0140] The polarizing film and polarizing plate of the present invention are suitable for use in liquid crystal display devices.

[0141] Description of Reference Numerals

[0142] 10 polarizing film

[0143] 201st protection layer

[0144] 30Second protection layer

[0145] 100 polarizing plates

Claims

1. A polarizing film, comprising a polyvinyl alcohol-based resin film containing a dichroic substance, The average polymerization degree of the polyvinyl alcohol resin contained in the polyvinyl alcohol resin film is 4200 or more. The single unit transmittance is 40.0% or more, and the polarization degree is 99.0% or more. The orientation function is 0.05 or more and 0.25 or less, The orientation function is measured by attenuated total reflection spectroscopy using a Fourier transform infrared spectrometer with polarized light as the measuring light, while the stretching direction of the polarizing film is parallel and perpendicular to the polarization direction of the measuring light. The absorbance spectrum obtained is 2941 cm -1 The strength is calculated by the following (Formula 1): (Formula 1)f=(3 <cos 2 θ>-1) / 2 =(1-D) / [c(2D+1)] =-2×(1-D) / (2D+1) In Formula 1, θ represents the angle of the molecular chain relative to the stretching direction; c represents (3cos 2 β-1) / 2; β represents the angle of transition dipole moment relative to the molecular chain axis, 2941cm -1 In the case of vibration, β is 90°; D represents (I ⊥ ) / (I / / ); I is the absorbance spectrum obtained relative to 3330cm -1 The absorption intensity of the reference peak is 2941 cm -1 The absorption intensity is expressed as (2941cm -1 Strength) / (3330cm -1 The value of the intensity of ⊥ I represents the case where the stretching direction of the polarizing film is arranged perpendicularly to the polarization direction of the measurement light, I / / The I represents the case where the stretching direction of the polarizing film is arranged parallel to the polarization direction of the measuring light. 2 . The polarizing film according to claim 1 , which has a thickness of 8 μm or less. 3 . The polarizing film according to claim 1 , which has a puncture strength of 35 gf / μm or more.

4. A polarizing film, which is composed of a polyvinyl alcohol-based resin film containing a dichroic substance, The single unit transmittance is 40.0% or more, and the polarization degree is 99.0% or more. Orientation function is 0.05 or more, puncture strength is 35gf / μm or more, The orientation function is measured by attenuated total reflection spectroscopy using a Fourier transform infrared spectrometer with polarized light as the measuring light, while the stretching direction of the polarizing film is parallel and perpendicular to the polarization direction of the measuring light. The absorbance spectrum obtained is 2941 cm -1 The strength is calculated by the following (Formula 1): (Formula 1)f=(3 <cos 2 θ>-1) / 2 =(1-D) / [c(2D+1)] =-2×(1-D) / (2D+1) In Formula 1, θ represents the angle of the molecular chain relative to the stretching direction; c represents (3cos 2 β-1) / 2; β represents the angle of transition dipole moment relative to the molecular chain axis, 2941cm -1 In the case of vibration, β is 90°; D represents (I ⊥ ) / (I / / ); I is the absorbance spectrum obtained relative to 3330cm -1 The absorption intensity of the reference peak is 2941 cm -1 The absorption intensity is expressed as (2941cm -1 Strength) / (3330cm -1 The value of the intensity of ⊥ I represents the case where the stretching direction of the polarizing film is arranged perpendicularly to the polarization direction of the measurement light, I / / The I represents the case where the stretching direction of the polarizing film is arranged parallel to the polarization direction of the measuring light. 5 . A polarizing plate comprising: the polarizing film according to claim 1 , and a protective layer disposed on at least one side of the polarizing film.

6. The method for producing a polarizing film according to any one of claims 1 to 4, comprising: A polyvinyl alcohol-based resin layer containing iodide or sodium chloride and polyvinyl alcohol-based resin is formed on one side of a long thermoplastic resin substrate to prepare a laminate; and The laminate is sequentially subjected to an air auxiliary stretching treatment, a dyeing treatment, an underwater stretching treatment, and a drying shrinkage treatment, wherein the drying shrinkage treatment is performed by heating the laminate while conveying the laminate in the length direction, thereby shrinking the laminate in the width direction by more than 2%, The total stretching ratio of the auxiliary in-air stretching treatment and the underwater stretching treatment is 3.0 to 4.0 times the original length of the laminate. The stretching ratio of the in-air auxiliary stretching treatment is greater than the stretching ratio of the underwater stretching treatment.

Citation Information

Patent Citations

  • Polarizing plate and method for manufacturing the same

    JP2001343521A

  • Protective film for polarizer and its manufacturing method

    JP2001343529A

  • Manufacturing method of thin polarizing film

    JP2012073580A

  • Transparent film

    WO2001037007A1

  • Method for producing polarizing film

    CN102859402A